Implementasi Tunnel GRE pada Jaringan Ring dan Mesh Perangkat Metro-E Nokia - R. Muhammad Arifin Arifin; Eni Dwi Wardhani; Samuel BETA (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
Tunnel is a technique of building a local communication path between two or more routers using a public IP network. The problems faced in tunneling systems are currently lacking guidelines for choosing the right technique according to the network topology used. In the electoral field, it is done based on experience or following SOPs. The brands of devices that support tunneling are very diverse in Indonesia, one of which is Nokia. This study focuses on the tunnel owned by Nokia devices, namely the GRE in order to produce guidelines for using the GRE tunnel. The analysis is carried out with various traffic engineering scenarios including no-load conditions, and various other conditions when there is a network outage. The results showed that the GRE without load runs normally. When the load from the beginning of the GRE gets a throughput of 0.995 Mbps and an average delay of 11.484 ms, when with a sudden load it gets a throughput of 1.059 Mbps and a delay of 11.386 and when a network disturbance is carried out with the ping command it gets 1 RTO. The GRE tunnel follows the LDP protocol path so it is suitable for use in new network implementations because of its simplicity in its configuration which is enough to activate the OSPF metric to balance traffic on each particular router interface